Younger Adults and Homeownership in Europe Through the Global Financial Crisis - Lennartz, Christian; Arundel, Rowan; Ronald, Richard (Population space and place, 2016)
In the context of poorly performing national economies and sustained employment insecurity since the Global Financial Crisis of 2007–2008, various UK and US studies have suggested that the transitions of younger people into independent living and into homeownership, in particular, have been in decline. Testing the wider validity of these findings for western European countries, this paper uses cross‐sectional European Union Statistics on Income and Living Conditions data to deconstruct to what extent and on which basis pre‐crisis to post‐crisis changes in the living arrangements of 18–34‐year olds have varied across 15 European Union countries. Our results confirm a common trend towards diminishing access to homeownership, bringing about larger rental sectors in many countries. Yet, we are far from observing the rise of a ‘Generation Rent’, because the stronger transformation process is one towards a higher share of younger adults living in co‐residence with their parents. Our empirical study further demonstrates that the directions of these shifts may vary strongly across countries, where the crisis has in some cases undermined existing residential patterns and forced realignment in the living arrangements among younger generations. Moreover, the study suggests that, although higher post‐crisis declines in young‐age homeownership is also associated with adverse labour market conditions, it seems to be primarily the volatility of more financialised housing markets that lead to increasing difficulties for younger people to realise housing property ownership. Copyright © 2015 John Wiley & Sons, Ltd.